Análise hamiltoniana de um modelo de partículas de Spin-2 massivas não-Fierz-Pauli - Rodrigues, Douglas Benndorf [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Neste trabalho abordamos de forma introdutória o tratamento de sistemas singulares, em especial as teorias de Maxwell, Proca e Fierz-Pauli, e obtemos resultados originais para a família de modelos de spin-2 massivos do tipo não-Fierz-Pauli. Tendo como ferramenta principal o método de Dirac para sistemas vinculados, escrevemos a densidade de hamiltoniana primária do modelo LnF P , obtemos seus vínculos primários, secundários, terciários e quartenários, assim como os multiplicadores de Lagrange. Calculamos também o número de graus de liberdade independentes e mostramos a positividade da hamiltoniana reduzida.

In this work, we approach in an introductory way the treatment of singular systems, especially the theories of Maxwell, Proca and Fierz-Pauli, and obtain original results for the non-Fierz-Pauli family of massive spin-2 models. Having as main tool the Dirac method for constrained systems, we write the primary Hamiltonian density of the LnF P model, obtain their primary, secondary, tertiary and quaternary constraints, as well as Lagrange multipliers. We calculate the number of independent degrees of freedom of the model and demonstrate the positivity of the reduced Hamiltonian.
Hamiltonian analysis of a non-Fierz-Pauli massive Spin-2 particles model
Keywords: Gravitação massiva; Fierz-Pauli; Spin-2; Método de Dirac; Relatividade geral; Massive gravity; Dirac method; General relativity